Teachers' and Students' Practices and Attitudes Toward Arabic (L1) Use in ELT - Qadri, Tahani (2006)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Tahani Abdul-Rahman Qadri Entitled, "Teachers' and Students' Practices and Attitudes Toward Arabic (L1) Use in ELT," June 2006. Thesis Advisor is Dr. Fatima Badry. Available are both Soft and Hard Copies of the Thesis.